LITERATURE REVIEW: PENGARUH SLEEP HYGIENE PRACTICE TERHADAP PENINGKATAN KUALITAS TIDUR PADA LANSIA - Puspita, Asih Purwandari Wahyoe; Fauziyah, Afro Salma; Amalia, Anggi Rojiah; Ahdiah, Danies Laelatul; Sabila, Fanny Fauziyyah; Bone, Maharani Pooja Natasya; Robani, Nida Nabila; Puspitasari, Nur Fatimah; Dewi, Prischa Amelliana; Gumilar, Risya Aisyah; Mu’minah, Siti; Suparto, Tirta Adikusuma; Nurhaliza, Rizkia Sukma (Yayasan Healing and Healthcare Education, 2025)
Introduction: Elderly people often experience sleep disorders that affect their physical and mental well-being. This decline in sleep quality is a common problem as we age. Sleep hygiene, as a non-pharmacological approach, focuses on behavioral and environmental changes to improve sleep quality. Aim: to conduct a systematic review to examine the effect of sleep hygiene activities on sleep quality in the elderly. Methods: The search was conducted using several databases including Google Scholar, Research Gate, Pubmed, and Science Direct from the past 4 years, namely 2020 to 2024. The keywords used were